Answer:
<u>The correct answer is b = 6 √3 units</u>
Step-by-step explanation:
Let's recall that we can use the following ratio for the sides of a 90 - 60 - 30 triangle:
1 : √3 : 2, where 2 is the hypotenuse.
Upon saying that, we have that in our triangle:
Hypotenuse = 12 units
a = 6 units
b = 6 √3 units
<u>The correct answer is b = 6 √3 units</u>
Answer:
{x,y} = {3/7,-43/7}
Step-by-step explanation:
System of Linear Equations entered :
[1] x + 3y = -18
[2] -x + 4y = -25
Graphic Representation of the Equations :
3y + x = -18 4y - x = -25
Solve by Substitution :
// Solve equation [1] for the variable x
[1] x = -3y - 18
// Plug this in for variable x in equation [2]
[2] -(-3y-18) + 4y = -25
[2] 7y = -43
// Solve equation [2] for the variable y
[2] 7y = - 43
[2] y = - 43/7
// By now we know this much :
x = -3y-18
y = -43/7
// Use the y value to solve for x
x = -3(-43/7)-18 = 3/7
Solution :
{x,y} = {3/7,-43/7}
Answer:
d
Step-by-step explanation:
because
Answer:
x=75
Step-by-step explanation:
We can use proportions to solve this problem. Put the side of the small triangle over the side of the large triangle.
42 50
------ = ----------
42+63 50+x
42 50
------ = ----------
105 50+x
Using cross products
42(50+x) = 50*(105)
2100+42x = 5250
Subtract 2100 from each side
2100-2100+42x = 5250-2100
42x =3150
Divide by 42
42x/42 = 3150/42
x = 75